Determination of iodine Value of Certain Polymers Using Chloramine-T as Reagent - Vasanta Kumar Pai, K.; Vasudeva Nayak, P.; Kumara Swamy, B.E. (Asian Journal of Chemistry, 2010)
Chloramine-T (CAT) has been used as the analytical reagent forthe determination of iodine value of certain polymer samples. Thesimple titrimetric method involves the treatment of polymer solutionwith an excess of CAT in the presence of glacial acetic acid (GAA),where quantitative addition of CAT to the olefinic bonds of thepolymer takes place. The unreacted CAT was determined iodometrically.